The NCCB Case Example: Reflections on a Successful Fourteen-Year CBPR Partnership - Alexis D. Jemal; Ellen Benoit; Shola Thompson; Heather A. Jones; Liliane Windsor; Teri Lassiter; Warren Thompson; The NJ Critical Consciousness Collaborative Board (3CB) (Journal of Participatory Research Methods)
The Newark Community Collaborative Board (NCCB) is in its fourteenth year of operation with nine successful research projects and more than six million dollars in funding. The NCCB began with a community needs assessment in Newark, New Jersey, that led to the subsequent establishment of a community collaborative board (CCB) of consumers, researchers, service providers, and residents committed to advocating for health equity through community engagement and research informed by critical thinking. This paper explores the NCCB’s history and processes that allowed conducting community-based participatory research (CBPR) to reduce inequities related to social determinants of health (SDH). This conceptual manuscript draws on data from NCCB meeting minutes and a group interview with three of the five founding members. We detail the collaborative process used to develop and assess Community Wise, a multilevel, group-based intervention designed to reduce substance use among formerly incarcerated men in Newark, funded by the National Institutes of Health. Review of documentation and interview transcripts revealed the following key ingredients for success: 1) Having a north star; 2) Functional diversity; 3) Challenges as learning opportunities; 4) Board structure and healthy relationships; and 5) Funding and resources. The NCCB has undergone multiple transformations, including a name change to the New Jersey Critical Consciousness Collaborative Board (NJ-3CB), representing its growth from being a small local board to becoming part of a network of community collaborative boards across the United States and a chapter of the global campaign against racism. These and future transitions will help sustain the collaborative journey.